Preparation, Structure and Physicochemical Properties of La0.95Bi0.05Mn1-yCuyO3+δ (у=0.1-0.4) and Composites with Bi2O3-Based Electrolytes - O. S. Kaimieva; V. V. Danilova; E. S. Buyanova; S. A. Petrova; I. V. Nikolaenko (Chimica Techno Acta)
Samples of La0.95Bi0.05Mn1-yCuyO3+δ (у=0.1-0.4) were prepared by solid-state synthesis. Additionally, the sample with nominal composition La0.95Bi0.05Mn0.7Cu0.3O3+δ was obtained using citrate-nitrate method. It was determined by X-ray diffraction analysis that the compounds have rhombohedral (space group R-3c) or orthorhombic (space group Pbnm) structure, depending on the composition. Single-phase compounds are synthesized at у=0.1; 0.2. The investigation using scanning electron microscope showed that the grain sizes for the samples sintered using different techniques are close to each other because of the high calcination temperature. For the sample with orthorhombic structure the phase transition into rhombohedral one was found around 390 °С by means of dilatometry. Thermal expansion coefficient of the sample La0.95Bi0.05Mn0.7Cu0.3O3+δ is equal to 6·10-6 K-1 (T 390 °C) and 15·10-6 K-1 (T 390 °C). The composite materials of substituted lanthanum manganites with Bi4V1.7Fe0.3O11-δ and Bi7Nb1.8Zr0.2O15.5-δ solid electrolytes were obtained at 650 °C. The electrical conductivity values for the latter one are by three orders of magnitude higher than for pure bismuth niobate.